Chemical Composition of Urinary Tract Stones: Experience in a Medical College Hospital, in Dhaka (Bangladesh Journal of Urology, 2020)
Objective: To find out the chemical composition of urinary tract stones in patients attending our hospital.Methods: A cross sectional hospital based study was conducted among 140 patients from October 2011 to September 2014 in SSMC & MH. The study included all patients of either gender and all ages who were diagnosed to have urinary tract stones and were managed in our hospital. Chemical analysis of stones were performed on stones, fragments, gravel’s passed spontaneously, or retrieved from endourological intervention or after ESWL or open surgery. Results were reviewed and analyzed with the help of SPSS17.Result: Out of 140 patients about one third (31.4%) were female and two thirds were (68.6%) male. Most of the patients belong to age group 40-50 years. Mean age of the patients was 43.74 years with standard deviation of 10.28 years. 20% of the patients have recurrent stones. By the type of symptoms all of the patients had loin or back pain. One third of the patients had (36.7%) calcium oxalet stones, more than one fourth of respondents (27.1%) had mixed stones and 12.9% had magnesium, ammonium phosphate stones. Calcium containing stones were the most(60%).Conclusion: Calcium containing stones constitute the most common variety of urinary tract calculi in our local population.Bangladesh Journal of Urology, Vol. 18, No. 1, Jan 2015 p.8-11